Wireless body area network for cycling posture monitoring - Maio, António José de Freitas (2016)
This work presents the design and implementation of a wireless body area network based on Bluetooth Low Energy (BLE) which enables the integration of multiple sensor nodes into a smartphone-based system in order to monitor the posture of cyclists. The wireless posture monitoring system presented in this chapter obtains the orientation in space of each body segment in which the sensor nodes are placed and calculates the trunk angle, the knee angle and the angle of inclination of the road. This system collects raw sensor data from accelerometers, magnetometers and gyroscopes and sends the data via BLE to an Android smartphone, which plays the role of central station and performs the data processing concerning the posture calculation. This chapter describes the development of the hardware and software of the sensor nodes, which are based on the CC2540 BLE system-on-chip, as well as the development of the Android application. Experimental results concerning the measurement of the posture of a cyclist are provided in order to validate the implementation.